Examining the differences between information professional groups in perceiving information ethics: An analytic hierarchy process study - Yueh, Hsiu-Ping; Huang, Ching-Yin; Lin, Weijane (Frontiers in Psychology, 2022)
Information and communication technology (ICT) has a great impact on contemporary society and people’s lives. Especially with the pervasive access to rapidly developing technology, the impact of ICT on society and human values, the norms of ICT use, and the ethical issues derived from them are beyond the past ethical framework and deserve more research attention. The purpose of this study was to explore the key factors that influence the decision-making behaviors of information professionals when they are faced with information ethics issues. The study adopted the analytic hierarchical process method to develop the evaluation framework and criteria for information professional ethics and employed the professional fields of library and information science and information technology as examples to compare whether information professionals in different fields make different judgments on the aforementioned decision-making criteria. The results of the study validated the professional information ethics hierarchy and criteria and contributed to the field of information ethics research by providing information on the aspects that need attention in the cultivation of professionals in different fields.